Chemistry in Forensics and Crime Solving: Review - Dina B. Abbas AL-Saedi (Journal of Global Pharma Technology, 2018)
Chemistry is one of the most important forensic sciences beside of the other evidence sciences, and it is focus on the chemical examination of chemical waste by different methods of analytical chemistry and instrumental analytical methods. In addition to the quantitative and qualitative analyzes, it is possible to perform a comparative and comparison between the different samples and the connection between them in different fields associated with crimes. Forensic chemistry includes organic and inorganic analysis, toxicology, arson investigation, and serology. Each method of analysis uses specialized techniques and instrumentation. The process may be as simple as setting up a density gradient column to compare soil samples or as complicated as using a mass spectrometer or neutron activation analysis to characterize an unknown substance.Keywords: Analytical chemistry, Forensic sciences, Toxicology, Finger print.